2018
DOI: 10.1016/j.htct.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori associated to unexplained or refractory iron deficiency anemia: an Egyptian single-center experience

Abstract: BackgroundRefractory or unexplained iron deficiency anemia accounts for about 15% of all cases. The endoscopic gastrointestinal workup sometimes fails to establish the cause of iron deficiency anemia and a considerable proportion of patients regardless of risk category fail to respond to oral iron supplementation. The aim of the present study was to assess the etiological role of Helicobacter pylori infection in adult Egyptian patients with unexplained or refractory iron deficiency anemia.MethodsA case control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 27 publications
1
23
0
1
Order By: Relevance
“…Demerdash et al, who enrolled 105 IDA patients and 70 age‐ and gender‐matched controls, clearly demonstrated a higher prevalence of H pylori infection in refractory IDA patients (61.5%) and a positive correlation with the mean corpuscular value (MCV; P = .046). Moreover, they observed a significant correlation between administration of anti‐ H pylori treatment plus iron and improvement of hemoglobin ( P < .001), MCV ( P < .001), iron ( P < .001), and ferritin levels ( P < .001) . Mwafy et al investigated 150 H pylori ‐positive patients (18‐50 years old) and 150 matched controls for several hematologic parameters, and they found significantly lower levels of iron in infected patients compared to uninfected (71.6 ± 24.8 vs 80.1 ± 20.7 μg/dL) and similar results were obtained for vitamin B12 levels (262.5 ± 100 vs 378.2 ± 160.6 pg/mL) .…”
Section: Hematologic Diseasesmentioning
confidence: 99%
“…Demerdash et al, who enrolled 105 IDA patients and 70 age‐ and gender‐matched controls, clearly demonstrated a higher prevalence of H pylori infection in refractory IDA patients (61.5%) and a positive correlation with the mean corpuscular value (MCV; P = .046). Moreover, they observed a significant correlation between administration of anti‐ H pylori treatment plus iron and improvement of hemoglobin ( P < .001), MCV ( P < .001), iron ( P < .001), and ferritin levels ( P < .001) . Mwafy et al investigated 150 H pylori ‐positive patients (18‐50 years old) and 150 matched controls for several hematologic parameters, and they found significantly lower levels of iron in infected patients compared to uninfected (71.6 ± 24.8 vs 80.1 ± 20.7 μg/dL) and similar results were obtained for vitamin B12 levels (262.5 ± 100 vs 378.2 ± 160.6 pg/mL) .…”
Section: Hematologic Diseasesmentioning
confidence: 99%
“…More recently, other authors worldwide reported the association between Helicobacter pylori infection and iron deficiency anemia. A recent study conducted in Mexico found a 7.8% prevalence of Helicobacter pylori infection in iron deficiency anemia patients referred to an academic hematology center [ 43 ], while an Egyptian study showed a higher prevalence of Helicobacter pylori infection in refractory iron deficiency anemia (61.5%) and a significant correlation between administration of anti- Helicobacter pylori treatment plus iron and improvement in terms of hemoglobin, mean corpuscular volume, iron, and ferritin levels [ 44 ]. A recent systematic review and meta-analysis showed that compared to uninfected subjects, Helicobacter pylori -infected individuals showed an increased likelihood of iron deficiency anemia (OR 1.72; 95% CI 1.23–2.42); and iron deficiency (OR 1.33; 95% CI 1.15–1.54), reporting increased ferritin levels following anti- Helicobacter pylori eradication therapy plus iron therapy as compared with iron therapy alone [ 45 ].…”
Section: The Role Of the Stomach In Non-bleeding-related Iron Defimentioning
confidence: 99%
“…Our sample consisted of a total of 7,829 patients, including both genders aged between 2 and 75 years. Studies from Egypt (n=18) [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] , Saudi Arabia (n=8) [46][47][48][49][50][51][52][53] , Lebanon (n=6) [54][55][56][57][58][59] , UAE (n=5) [60][61][62][63][64] , Iraq (n=3) [65][66][67] , Qatar (n=3) [68][69][70] , Algeria (n=2) 71,72 , Palestine (n=1) 73 , Morocco (n=1) 74 , Syria (n=1) 75 , Yemen (n=1) 76 Tunisia (n=1) 77…”
Section: Patients and Study Characteristicsmentioning
confidence: 99%